Activation of Transforming Growth Factor β by Malaria Parasite-derived Metalloproteinases and a Thrombospondin-like Molecule - Omer, Fakhreldin M. (The Rockefeller University Press, 2003)
Much of the pathology of malaria is mediated by inflammatory cytokines (such as interleukin 12, interferon γ, and tumor necrosis factor α), which are part of the immune response that kills the parasite. The antiinflammatory cytokine transforming growth factor (TGF)-β plays a crucial role in preventing the severe pathology of malaria in mice and TGF-β production is associated with reduced risk of clinical malaria in humans. Here we show that serum-free preparations of Plasmodium falciparum, Plasmodium yoelii 17XL, and Plasmodium berghei schizont-infected erythrocytes, but not equivalent preparations of uninfected erythrocytes, are directly able to activate latent TGF-β (LatTGF-β) in vitro. Antibodies to thrombospondin (TSP) and to a P. falciparum TSP-related adhesive protein (PfTRAP), and synthetic peptides from PfTRAP and P. berghei TRAP that represent homologues of TGF-β binding motifs of TSP, all inhibit malaria-mediated TGF-β activation. Importantly, TRAP-deficient P. berghei parasites are less able to activate LatTGF-β than wild-type parasites and their replication is attenuated in vitro. We show that activation of TGF-β by malaria parasites is a two step process involving TSP-like molecules and metalloproteinase activity. Activation of LatTGF-β represents a novel mechanism for direct modulation of the host response by malaria parasites.